Experimental study on flow-induced vibration response characteristics of leaching tubing in salt cavern gas storage. (August 2022) - Liu, Jun; Zeng, Linlin; Guo, Xiaoqiang; Dai, Liming; Huang, Xiao; Cai, Ling
Highlights: A laboratory experimental device for flow-induced vibration of leaching tubing was developed based on similarity principle. The influences of main operation parameters on the vibration characteristics of leaching tubing were analyzed systematically. The research results provide theoretically guidance for practical application of leaching tubing in salt cavern gas storage. Abstract: To address flow-induced vibration failure problems of water solution leaching tubing string in salt cavern gas storage, a laboratory experimental device for flow-induced vibration of leaching tubing string was developed based on the similarity principle, and the corresponding experimental bench was built, according to the on-site parameters of the M gas storage well in Jianghan Oilfield, China. The vibration simulation experiments were carried out, and the displacement and amplitude-frequency response data at the bottom end of the tubing string were measured. The influences of different operation parameters and structure modes, such as water injection flow rate, two-port distance, screen structure and circulation mode, on the vibration characteristics of the tubing string were explored, the failure mechanism of the leaching tubing string was revealed, and the corresponding vibration failure control methods were proposed. The results obtained demonstrate that, first, at the moment of pump start-up (corresponding to well opening on-site), the tubing string produced obvious water hammer phenomenon. With the increase of the water injection flow rate, the vibration displacement and frequency of the center tube first increase and then decrease, when the water injection flow rate is less than 1.55 L/min (corresponding to the on-site flow rate of 40 m 3 /h), the risk of vibration failure of leaching tubing can be reduced. Second, when the two-port distance is greater than 0.16 m (corresponding to the on-site two-port distance of 45 m), the amplitude and frequency of lateral vibration of the center tube increase significantly, and the risk of lateral vibration deformation of leaching tubing increases. Third, adding a symmetrical hole screen at the bottom of the center tube can significantly reduce the vibration displacement and frequency of leaching tubing, and improve the safety of the operation tubing string. Fourth, the vibration displacement and amplitude of the leaching tubing in the reverse circulation mode are smaller than those in the positive circulation mode. When the cavern shape requirements are met on-site, the vibration of the tubing string can be effectively reduced by using the reverse circulation cavern leaching.